Treatment Patterns of Diabetes in Italy: A Population-Based Study - Moreno Juste, Aida; Menditto, Enrica; Orlando, Valentina; Monetti, Valeria Marina; Gimeno Miguel, Antonio; González Rubio, Francisca; Aza–Pascual-Salcedo, María Mercedes; Cahir, Caitriona; Prados Torres, Alexandra; Riccardi, Gabriele (Frontiers in Pharmacology, 2019)
Background: The steady increase in type 2 diabetes prevalence and the availability of new antidiabetic drugs (AD) have risen the use of these drugs with a change in the patterns of specific drug utilization. The complexity of this treatment is due to successive treatment initiation, switching and addition in order to maintain glycaemic control. The purpose of this study was to describe the utilization patterns of ADs at initiation, treatment addition and switching profiles and to measure factors influencing persistence to therapy. Methods: Retrospective observational study. Data were retrieved from the Campania Regional Database for Medication Consumption. Population was composed by patients receiving at least one prescription of ADs between January 1 and December 31, 2016. We calculated time to treatment switching or add-on as median number of days and interquartile range (IQR). Persistence rates were estimated using the Kaplan-Meier method. We used Cox regression models to estimate the likelihood of non-persistence over one year of follow-up. Hazard ratios and 95% confidence intervals were calculated. Results: Of 14,679 subjects, 86.9% started with monotherapy and 13.1% with combination therapy. Most common initial treatment was metformin, both in monotherapy and combination therapy. First-line prescription of sulfonylurea was observed in 6.9% of patients aged 60-79 years and in 10.8% of patients aged ≥80 years. Patients starting with metformin showed fewer treatment modifications (10.4%) compared to patients initiating with sulfonylureas (35.2%). Newer ADs were utilized during treatment progression. Subjects initiated with sulfonylurea were approximately 70% more likely to discontinue treatment compared to those initiated on metformin. Oldest age group (≥80years) was more likely to be non-persistent and likelihood of non-persistence was highest in polymedicated patients. Patients changing therapy were more likely to be persistent. Conclusions: Our results show that treatment of T2D in Italy is consistent with clinical guidelines. Even if newer ADs were utilized during disease progression, they seem not to be preferred in patients with a higher comorbidity score although these patients could benefit from this kind of treatment. Our study highlights patients’ characteristics that may help identify those who would benefit from counselling from their health-care practitioner on better ADs usage.